2019
DOI: 10.1177/1753193419826465
|View full text |Cite
|
Sign up to set email alerts
|

Experience of nail bed injuries at a tertiary hand trauma unit: a 12-month review and cost analysis

Abstract: The aim of this study was to analyse the management of nail bed injuries from a clinical and economic perspective. We carried out a retrospective analysis of nail bed injuries treated operatively at a tertiary Plastic Surgery Hand Trauma Unit during 2016. The National Schedule of Reference Costs (2015–2016) was used to estimate the costs of treating 630 patients. The most common mechanism was a crush injury in a door (33%). Fifty-five per cent of patients had an associated tuft fracture. The minimum cost per a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In our study, we found that sports was the most common hobby amongst the study participants. This was like the findings in a study done by Yildirimer L et al, 5 where injuries due to sports related trauma (crush injuries) was a leading cause of nail dyschromia.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that sports was the most common hobby amongst the study participants. This was like the findings in a study done by Yildirimer L et al, 5 where injuries due to sports related trauma (crush injuries) was a leading cause of nail dyschromia.…”
Section: Discussionsupporting
confidence: 89%
“…Depending on the injury mechanism we will have to consider possible associated injuries. Fingertip injuries most frequently result from a crush injury, often from the hinge side of a door [5]. Approximately 50% of nail bed injuries presenting to hospital are associated with distal phalangeal fractures [6].…”
Section: Nail Trauma Assessmentmentioning
confidence: 99%
“…On the other hand, stress wounds are prone to ischemia and hypoxia, and matrix metalloproteinases are constantly activated, which will cause the decomposition of cell growth factors and affect the growth and proliferation of epidermal cells, making wound recovery difficult [ 11 ]. Western medicine usually adopts debridement treatment, surgical intervention, electrical stimulation, biotechnology, and negative pressure wound therapy to carry out wound recovery treatment [ 12 ]. Western medicine treatment causes great damage to the body, with higher costs and more side effects.…”
Section: Introductionmentioning
confidence: 99%